Learning style preferences among online distance learning (e-PJJ) bachelor degree students in Faculty of Health Sciences UiTM Puncak Alam / Siti Khuzaimah Ahmad Sharoni, Beinah Karim and NurJariyah Hamzah - Ahmad Sharoni, Siti Khuzaimah; Karim, Beinah; Hamzah, NurJariyah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
This study aimed to determine learning style preferences among online distance learning (e-PJJ) bachelor degree students in the Faculty of Health Sciences UiTM Puncak Alam and its’ relationship with students’ characteristic likes age, gender, marital status, program, semester, study hours per day, Cumulative Grade Points Average (CGPA) and number of days absent in class (last semester). Data collection is obtained from 201 e-PJJ students involved in five programs of Health Sciences. Gathered data was entered and analyzed by using the statistical package for the social science (SPSS) version 21 software. In this study, it is set out that perceptive is the most preferred learning style among ePJJ students then followed by imaginative, analytic, solitary and competitive. Significant differences were found in competitive and imaginative learning styles with gender (p<0.05). Competitive learning style and marital status, its’ showed a significant difference (p<0.05). Imaginative learning style showed a weak correlation with CGPA (rs=-0.140, p=0.047). The perceptive learning style also presented a weak correlation with study hours (rs=-0.159, p=0.024). In general, learning style preferences were influenced by students’ characteristics. Therefore, it can be suggested that further comprehensive research is needed to understand the important factors that influenced learning style preferences among online distance learning (e-PJJ) students.